THE THEORETICAL PERSPECTIVE OF PRICES AND PRICING PROCESS (Development Service Industry Management, 2024)
Pricing is an integral part of the business strategy of any enterprise, determines the successful positioning of products, allows to achieve business goals quickly, ensure the effective functioning of the company. At the same time, it is a well-known fact that pricing is the area where mistakes and miscalculations most often occur. In order to study the pricing process, we analyzed the works of domestic and foreign scientists, identified aspects that affect the process and outcome of pricing, outlined a list of stages. The pricing process can be conducted for both existing goods (which are already on the market) and new goods (which are currently being launched). New products and services are the result of technological development, create new characteristics of quality, productivity, cost, methods of promotion, so pricing for such products has its own specific features. Note that an important role in the pricing of such products is played by the lack of a base for comparison, the complexity of calculating the percentage of profit in price. Particular attention in the article is paid to pricing methods, which, according to classification approaches, can be divided into different groups. In foreign literature, pricing is often distinguished on the basis of costs, competition and value-based. We investigated the positive and negative features of such methods, the specifics of their use in different markets. We also described a group of parametric methods which are used for goods that have analogues on the market. The concept behind cost pricing methods is that the price base is the sum of expenses and the desired profit amount. The main disadvantages of this group of pricing methods are the low validity of the costs proposed for inclusion in the price, frequent errors in calculating the profitability of products, the inadequacy of the margin, the loss in price competition. The main advantages of market pricing methods are that they are established on the basis of a balance of interests, the willingness of consumers to pay a specific price for a product or service, they make it possible to respond to changes in the market situation. But, in the same advantages, we can see threats. In particular, the need to monitor the situation on the market (consumer reaction, the presence of new competitors, etc.), variability, susceptibility to instability of such prices, focus on the short term period. The threat of value-based pricing is that if a company believes that it is passing on value through its prices and customers, on the other hand, do not perceive value as being related to set prices. In this case, the company's price target is defeated.The main task for managers is to find a balance between the price that corresponds to the level of consumer satisfaction and the price that provides the desired level of profit for the enterprise and covers all costs.This is a complex task that requires careful analysis of the market, consumer behavior (including their reaction to price changes), and effective determination of production costs. We also noted that in literary sources there is often no mechanism for providing such an analysis, which will become a prospect for further research and developments.
Keywords: price; pricing process; pricing methods